THE INFLUENCE OF INDIVIDUAL PERSONALITIES TOWARDS TEAM PERFORMANCE AT PT. BPR PRISMA DANA MANADO - Untu, Mario Rahmat (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
In today’s global and competitive environment, one of the more often debated issues in the study of organizational behavior is the effects of workforce diversity such as personality on team performance. Workforce diversity refers to employee’s individual differences and similarities. It stands for individuality that includes personality, gender, race, nationality, ethnicity, region, income, marital status, work experience, perceptions among others. The purpose of this study was to examine how individual personality impact on team performance. The target population of this study consisted of employees of Prisma Dana (PT. BPR). Questionnaire was used to select a sample of 30 employees of BPR Prisma Dana Manado. The findings on the individual personality towards team performance showed that the extraversion personality trait is the most predictive of job performance at followed by conscientiousness, openness to experience, emotional stability and agreeableness. In conclusion, the majority of BPR Prisma Dana’s workforce is mainly composed of an extraversion personality trait, which has been found most predictive of job performance at the organization. The management party of BPR Prisma Dana need to consider about the importance on emotional stability of the employee, regarding with it in advanced.   Keywords: personality, performance, organizational behavior.